2016
DOI: 10.1186/s12909-016-0795-x
|View full text |Cite
|
Sign up to set email alerts
|

The Haiti Medical Education Project: development and analysis of a competency based continuing medical education course in Haiti through distance learning

Abstract: BackgroundRecent calls for reform in healthcare training emphasize using competency-based curricula and information technology-empowered learning. Continuing Medical Education programs are essential in maintaining physician accreditation. Haitian physicians have expressed a lack access to these activities. The Haiti Medical Education Project works in alliance with Haitian medical leadership, faculty and students to support the Country’s medical education system. We present the creation, delivery and evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Teleconferences with trainees at remote sites using VideoConferencing technology [37]; • An innovative model of Virtual Business Projects (VBP) based on teamwork [38]; • Remote online lessons based on technologies of synchronous and asynchronous remote communication [39]; • Model of intelligent learning "Monitoring the environmental parameters in a Smart City", which, among other things, provides the creation of remote laboratories for students and so forth [40]; • Creation of breakthrough technologies using virtual reality (VR) environment, games and educational programs, leading to a creative result [41,42].…”
mentioning
confidence: 99%
“…Teleconferences with trainees at remote sites using VideoConferencing technology [37]; • An innovative model of Virtual Business Projects (VBP) based on teamwork [38]; • Remote online lessons based on technologies of synchronous and asynchronous remote communication [39]; • Model of intelligent learning "Monitoring the environmental parameters in a Smart City", which, among other things, provides the creation of remote laboratories for students and so forth [40]; • Creation of breakthrough technologies using virtual reality (VR) environment, games and educational programs, leading to a creative result [41,42].…”
mentioning
confidence: 99%
“…Finally, while the DE modality carries new learning opportunities, it is still a study field that lacks further investigation. In medical education, research has already indicated that the use of technologies and mixed learning methods, or syllabi with complementary activities online, enhance learning ( Boye et al, 2012 ; Heiman et al, 2012 ; Van Doorn and Van Doorn, 2014 ; Battat et al, 2016 ). Positive results using the online space for inter-professional education and collaborative cooperative learning were also observed by students ( Solomon et al, 2010 ; Shendell et al, 2016 ; Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…É necessário um método instrutivo robusto, com características pedagógicas positivas. Assim, propomos um método pedagogicamente estruturado para AVA, que inclui uma leitura inicial motivadora (Crônica Médica -CM) e um programa de construção de conhecimento, utilizando casos reais juntamente com recursos audiovisuais (Oficina Diagnóstica -OD Recently, there has been evidence of increased investment in Web-Based Medical Education (WBME) worldwide, following the globalization promoted by the Internet and the numerous teaching-learning opportunities available 3,4,5 . WBME is gaining increasing acceptance through activities and courses offered by Virtual Learning Environments (VLEs).…”
Section: Contextounclassified